Strongly correlated electron system NiWO4: A new family of materials for triboelectrics using inherent Coulombic repulsion - Han, Gi Hyeon; Park, Sang Jeong; Park, Gi Hyun; Park, Chul Oh; Lee, Heejun; Lee, Jae Won; Bang, Joonho; Lee, Kimoon; Chun, Dong Won; Kim, Sung Wng; Lee, Seung Yong; Lee, Kyu Hyoung (Elsevier BV, 2024)
The strongly correlated electron system (SCES) insulators promise a wide range of intriguing physical phenomena arising from the exotic charge gap depending on the strength of the Coulombic repulsion between d and f orbital cations. The SCES exhibits polaron hopping conduction, which requires a higher activation energy for carrier conduction between nearest cations, indicating a strong insulating character with relatively high permittivity. Here, we demonstrate that the NiWO4 SCES insulator, which is formed by Coulombic repulsion between the nearest d orbital of Ni, proposes a suitable triboelectric material unlisted system from conventional metal oxides. The higher degree of freedom in NiWO4 by the lower symmetry of monoclinic structure and an additional selection of composition exhibits high relative permittivity (similar to 13.8) in a wide range of temperatures (up to 180 degree celsius). The optimized simple mixture of NiWO4 and PDMS (polydimethylsiloxane) for the negatively charged material to triboelectric nanogenerator (TENG) presents 1.78 times higher output compared to the pristine PDMS film-based TENG. NiWO4, considering the physical properties of the SCES determined by Coulombic repulsion strength, paves the way for a new option of TENG materials following the high permittivity.